2022
DOI: 10.25134/erjee.v10i2.6253
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning Vocapp: (Vocabulary Application) for English Vocabulary Learning

Abstract: The background of this research is to investigate the urgency of vocabulary as the most important aspect in language. In this research, vocabulary learning will be assisted by using an android application, namely VocApp; (Vocabulary Application). The purpose of this research and development is to (1) identify the needs of vocabulary learning media according to teachers and students, (2) know the principles of developing learning media based on theoretical studies, identify needs and analyze existing learning m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…They developed an android application for English vocabulary learning for primary school students and found that this application was effective and strongly suggested use to support teaching and learning activities for vocabulary. Moreover, the smartphone application (VocApp) designed by Badroeni, et al (2022) also significantly improved students' skills in bulding vocabulary. The researchers created the application for SMP Negeri I Kuningan with a total of 29 students.…”
Section: Introductionmentioning
confidence: 98%
“…They developed an android application for English vocabulary learning for primary school students and found that this application was effective and strongly suggested use to support teaching and learning activities for vocabulary. Moreover, the smartphone application (VocApp) designed by Badroeni, et al (2022) also significantly improved students' skills in bulding vocabulary. The researchers created the application for SMP Negeri I Kuningan with a total of 29 students.…”
Section: Introductionmentioning
confidence: 98%